Money for nothin' and coal for free: 'Technology neutrality' and biomass development under the Flemish tradable green certificate scheme. (March 2016) - Carton, Wim
Abstract: Recent literature has highlighted the creation of multiple equivalences as an important factor underpinning the rise of market-based mechanisms for environmental regulation. Extending these insights into the field of renewable energy policy, this article focuses on one example of this trend – namely the principle of technology neutrality as applied under the Flemish tradable green certificate scheme – and analyzes the concrete ways in which it has shaped the evolution of the Flemish renewable energy landscape. Concretely, the article shows that technology neutrality played a key role in promoting the uptake of biomass combustion in old coal power plants in Flanders, which led to a number of undesirable outcomes and gave rise to significant opposition. Correcting these shortcomings required a number of policy interventions on the part of the Flemish government that fundamentally moved the scheme away from the principle of technology neutrality and towards a more hybrid RE support system, suggesting that the promotion of technology neutrality was fundamentally misguided. Together with similar experiences from related market-based instruments, this suggests that the promotion of technology neutrality has far-reaching implications for the environmental effectiveness of climate and energy policies. In light of the continued promotion of the principle, the article calls for full recognition of the inherent technological choices that are being made through the promotion of policies that purport to be technology-neutral.